Gastroesophageal Reflux in Asymptomatic Patients with Diabetes: An Impedance Study Diabetes, Obesity and Gastroesophageal Reflux - Gokturk, Suut; Akyuz, Filiz; Arici, Serpil; Alpaslan, Busra; Ormeci, Asli; Soyer, Ozlem Mutluay; Evirgen, Sami; Cavus, Bilger; Uzum, Ayse Kubat; Gul, Nurdan; Akyuz, Umit; Karaca, Cetin; Demir, Kadir; Kaymakoglu, Sabahattin; Satman, Ilhan; Besisik, Fatih (Experimental and Clinical Endocrinology & Diabetes, 2020)
Introduction Gastroesophageal reflux disease (GERD) is more frequent in patients with diabetes mellitus (DM).The aim of the present study was to evaluate gastroesophageal reflux (GER) in asymptomatic patients with DM using 24-h pH impedance.Materials and Methods 19 healthy controls and 35 patients with DM without typical GERD symptoms were enrolled in the study. A 24-h pH-impedance study, esophageal manometry and gastroscopy were performed on all patients with DM. In the control group, an impedance study was performed on all subjects, and gastroscopy and esophageal manometry were performed on those who consented to the procedures. Patients with diabetes were categorized as obese [body mass index (BMI)>30 kg/m2] or non-obese (BMI<30 kg/m2) and both groups were compared with healthy controls.Results The mean BMI was similar in the control group (27.3±2.6 kg/m2) and the diabetic group (28.7±5 kg/m2) (p>0.05).Erosive esophagitis was found in 7.5% of the DM group. Esophageal dysmotility was higher in diabetics compared to the control group (45.5 vs. 11%, p=0.04). Neuropathy was found to be an independent risk factor for dysmotility. The mean DeMeester score (DMS) (25.6±32.5 vs. 11.2±17, p=0.01) and bolus exposure time (2.1±1.3 vs.1.3±1.3 min, p=0.009) were higher in the DM group compared with the control group.The difference was mainly observed between obese diabetics and the control group (p<0.05). The mean DMS, pathologic acid reflux, and esophageal dysmotility rate were higher in patients without complications of DM (p<0.05). BMI was higher in these patients than in patients with complications.Conclusion Acid reflux is common in patients with diabetes.GER is associated with the existence of obesity rather than hyperglycemia.
Keywords: diabetes; esophageal pH monitorizing; gastroscopy; esophageal manometry; obesity